Implementation fidelity of the Falls Management Exercise Programme: a mixed methods analysis using a conceptual framework for implementation fidelity. (August 2021) - Orton, E.; Lafond, N.; Skelton, D.A.; Coupland, C.; Gladman, J.R.F.; Iliffe, S.; Logan, P.A.; Masud, T.; Timblin, C.; Timmons, S.; Kendrick, D.
Abstract: Objectives: Falls in older adults cause significant morbidity and mortality and incur cost to health and care services. The Falls Management Exercise (FaME) programme is a 24-week intervention for older adults that, in clinical trials, improves balance and functional strength and leads to fewer falls. Similar but more modest outcomes have been found when FaME is delivered in routine practice. Understanding the degree to which the programme is delivered with fidelity is important if 'real-world' delivery of FaME is to achieve the same magnitude of outcome as in clinical trials. The objective of this study was to examine the implementation fidelity of FaME when delivered in the community to inform quality improvement strategies that maximise programme effectiveness. Study design: A mixed methods implementation study of FaME programme delivery. Methods: Data from programme registers, expert observations of FaME classes, and semistructured interviews with FaME instructors were triangulated using a conceptual framework for implementation fidelity. Quantitative data were analysed using descriptive statistics. Interviews were transcribed verbatim and analysed using thematic analysis. Results: In total, 356 participants enrolled on 29 FaME programmes, and 143 (40%) participants completed at least 75% of the classes within a programme. Observations showed that 72%–78% of programme content was delivered, and 80%–84% quality criteria were met. Important content that was most often left out included home exercises, Tai Chi moves, and floor work, whereas quality items most frequently missed out included asking about falls in the previous week, following up attendance absence and explaining the purpose of exercises. Only 24% of class participants made the expected strength training progression. Interviews with FaME instructors helped explain why elements of programme content and quality were not delivered. Strategies for improving FaME delivery were established and helped to maintain quality and fidelity. Conclusions: FaME programmes delivered in the 'real world' can be implemented with a high degree of fidelity, although important deviations were found. Facilitation strategies could be used to further improve programme fidelity and maximise participant outcomes.